LITERATURE OF REVIEWINFLUENCE OF TRANSFORMATIONAL LEADERSHIP, WORK ENVIRONMENT, ON EMPLOYEE PERFORMANCE AT PT. BERINGIN JAYA - Sabrina Fitria Novianty; Muhammad Richo Rianto (Draf Solusi Indonesia, 2023)
As changes in the business environment becomeincreasingly rapid in the era of globalization,companies must demonstrate the ability to adapt inorder to be able to compete with other companies.The success of a company or organization is largelydetermined by the human resources it has. In thiscase human resources are employees. Employees arean important asset for a company because thepresence of competent employees helps thecompany achieve its goals. PT. Beringin Jaya isheadquartered in Bekasi City, the company operatesin the field of steel bars and reinforcement. BeringinJaya found that employees felt the leadershipenvironment was less supportive, which affectedtheir performance. The type of research used in thisresearch is Quantitative Research with descriptivemethods. The population in this study wereemployees of PT. Beringin Jaya, numbering 56 people.The number of samples to be studied in this researchis determined using the Slovin formula. Based oncalculations carried out, the number of samples inthis study was 49 people